2022
DOI: 10.5194/esurf-10-81-2022
|View full text |Cite
|
Sign up to set email alerts
|

Sediment export in marly badland catchments modulated by frost-cracking intensity, Draix–Bléone Critical Zone Observatory, SE France

Abstract: Abstract. At the interface between the lithosphere and the atmosphere, the critical zone records the complex interactions between erosion, climate, geologic substrate, and life and can be directly monitored. Long data records (30 consecutive years for sediment yields) collected in the sparsely vegetated, steep, and small marly badland catchments of the Draix–Bléone Critical Zone Observatory (CZO), SE France, allow analyzing potential climatic controls on regolith dynamics and sediment export. Although widely a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 54 publications
(67 reference statements)
2
22
0
Order By: Relevance
“…The mountainous climate and easily erodible lithology induce a strong seasonal pattern in regolith formation and sediment export. During winter, regolith is formed mainly due to frost-cracking processes (Ariagno et al, 2022), leading to a heterogeneous surface and desiccation features, as also observed in similar Spanish badlands (Nadal-Romero & Regüés, 2010;Regüés et al, 1995). Spring flash floods induce a peak in sediment export (Ariagno et al, 2022;Mathys, 2006).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…The mountainous climate and easily erodible lithology induce a strong seasonal pattern in regolith formation and sediment export. During winter, regolith is formed mainly due to frost-cracking processes (Ariagno et al, 2022), leading to a heterogeneous surface and desiccation features, as also observed in similar Spanish badlands (Nadal-Romero & Regüés, 2010;Regüés et al, 1995). Spring flash floods induce a peak in sediment export (Ariagno et al, 2022;Mathys, 2006).…”
Section: Introductionmentioning
confidence: 68%
“…The higher values of D50 and resistance at the end (Feb20) compared to the beginning (Nov19) of the winter season is interpreted as a lack of weathering of the regolith. As frost‐cracking has been inferred to be the main physical weathering process in this catchment (Ariagno et al, 2022), we computed the frost‐cracking intensity indicator (FCI) for both winters, following the approach of Ariagno et al (2022). Between the campaigns of November 2019 and February 2020, we found an FCI of about −11°C min/cm on south‐facing slopes, whereas for the same period during winter 2020–2021 and 2021–2022 the FCI is about −411°C min/cm and −866°C min/cm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations